The Effectiveness of a Cognitive Learning-Teaching Program on Cognitive Speed among Female Students in Primary Education Colleges - Dr. Naz Badr Khan Al-Sindi; Nwaal Abbas Akal (Migration Letters, 2023)
The current study aims to investigate the effectiveness of a cognitive-based instructional program on cognitive development speed among female students majoring in elementary education. The research sample comprised 91 female students, selected to represent the experimental group, consisting of 47 students, and the control group, consisting of 44 students from the Department of Early Childhood Education, Second Stage, College of Elementary Education, Mustansiriya University. The researcher adopted a cognitive speed test consisting of three cognitive assessments, originally developed and translated by Al-Sharqawi (1983), in their final format, with 30 items for each test, distributed among the Visual Similarity Test, the Visual Association Test, and the Three-Dimensional Length Estimation Test. The researcher verified the psychometric properties of the scale and subsequently applied it to the research sample. Several statistical methods were employed to achieve the research objectives, including Chi-square, Independent Samples t-test, and Cronbach’s alpha. The results revealed that second-stage female students majoring in Early Childhood Education exhibited varying levels of cognitive speed.